APPROACHES TO THE STUDY OF THE DEVELOPMENT OF SCIENCE AND CULTURE IN THE ISLAMIC WORLD - Abdullayev Abdurasul Abdulpattoyevich (Modern American Journals, 2025)
This article describes the flourishing of science and culture in the Islamic world, Muslims' attitude towards knowledge as the highest value, the role of science and culture in the formation and development of Islamic civilization, and explains that the flourishing of science and culture in the Islamic world occurred not through religious laws and rules themselves, but through its complex socio-historical activities, reform movements related to freedom of thought, and scientific dialogue with external civilizations. It is also recognized that today scientists of developed Western countries recognize that science and culture spread throughout the world through Islam, the flourishing of national cultures is associated with the spread of science and enlightenment with the Islamic religion.
Keywords: Civilization, Muslim culture, caliph, global, societal development, religious conservatism.